AB0542 Multiple sclerosis in patients with primary sjÖgren's syndrome. (12th June 2018) - Kaltsonoudis, E.; Pelechas, E.; Konitsiotis, S.; Voulgari, P.V.; Drosos, A.A.
Abstract : Background: Imaging and histopathologic studies in patients with primary Sjögren's Syndrome (pSS) have demonstrated white matter lesions which are indistinguishable from those observed in multiple sclerosis (MS). Objectives: The purpose of this study was to evaluate the frequency of MS in a cohort of patients with pSS. Methods: One hundred and twenty-one patients with pSS had been evaluated and followed up in the outpatient Rheumatology Clinic at predefined times since 1994. All patients were classified according to the 2016 ACR-EULAR criteria for SS. During follow-up the clinical, laboratory and imaging findings were all recorded. In addition, Magnetic Resonance Imaging and electrophysiological studies as well as spinal fluid analysis were performed when indicated. The diagnosis of MS was based on the 2010 revised McDonald criteria. Results: Seven patients were diagnosed as having MS. All patients with MS were female. Mean age at the time of MS diagnosis was 65.5±3.6 years, while pSS has been diagnosed at the mean age of 54.4±3.2 years. Mean time of MS development was approximately 10 years after the pSS diagnosis. pSS patients who developed MS had severe sicca symptoms without other extraglandular manifestations and had positive Ro (SSA) antibodies and a positive minor salivary gland biopsy. pSS patients with MS development were treated appropriately in the Neurology department with biological medications with some improvement of the sicca symptoms. Conclusions: We found that 5.8% of pSS patients as having MS. This percentage of patients clearly indicates the possibility for the coexistence of a second autoimmune disease with similar if not common pathogenetic mechanisms. Thus patients with pSS should be evaluated carefully and screened appropriately for MS when indicated. Disclosure of Interest: None declared